POLA KOMUNIKASI PADA PAGUYUBAN FU HE AN DALAM REGENERASI KESENIAN WAYANG POTEHI DI KLENTENG HONG SAN KIONG KECAMATAN GUDO KABUPATEN JOMBANG - Rohmah, Amalia Nur; Huda, Anam Miftakhul (Universitas Negeri Surabaya, 2022)
Research on Communication Patterns in the Fu He An Association in the Regeneration of Puppet Potehi Arts at the Hong San Kiong Temple, Gudo District, Jombang Regency. This study uses an ethnographic method of communication which will facilitate data collection. Through the Fu He An Association, researchers used the ethnographic method of communication by focusing on communication activities contained in the object of research, namely communication situations, communication events, and acts of communication. Data collection is done through interviews and also observation or observation. In this study, it is known that the communication pattern carried out by the Fu He An Association in regenerating the Wayang Potehi art is a wheel communication pattern and a star communication pattern with two-way or reciprocal communication flows. This communication pattern is found in the relationship between the leader of the association and the dalang, musician, and prospective dalang (wheel communication pattern) and the relationship between the dalang, musician, and prospective dalang in learning and performing Wayang Potehi performances (stellar communication pattern). Keywords: Communication Pattern, Fu He An Association, Regeneration, Potehi Puppet.